2021
DOI: 10.1038/s41598-021-91205-3
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal preference and depressive symptomatology: a meta-analysis

Abstract: Eveningness, a preference for later sleep and rise times, has been associated with a number of negative outcomes in terms of both physical and mental health. A large body of evidence links eveningness to Major Depressive Disorder (MDD). However, to date, evidence quantifying this association is limited. The current meta-analysis included 43 effect sizes from a total 27,996 participants. Using a random-effects model it was demonstrated that eveningness is associated with a small effect size (Fisher’s Z = − 2.4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 106 publications
1
13
0
1
Order By: Relevance
“…Furthermore, evening subjects also showed the highest prevalence of all measured psychological symptoms. These findings agree with previous studies suggesting a relationship between evening chronotype and increased anxiety and depression symptom severity [39][40][41][42]. The mechanisms governing the relationship between chronotype and the pathophysiology of depression, however, are still not fully understood.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, evening subjects also showed the highest prevalence of all measured psychological symptoms. These findings agree with previous studies suggesting a relationship between evening chronotype and increased anxiety and depression symptom severity [39][40][41][42]. The mechanisms governing the relationship between chronotype and the pathophysiology of depression, however, are still not fully understood.…”
Section: Discussionsupporting
confidence: 92%
“…Given our findings, it is necessary to consider how wake times may be important in relation to coping. Chronotype [i.e., one's preference for waking up and going to bed earlier or later (36)] shows a range of natural variation across individuals and has been linked to mood disruption, although primarily in adult studies (37)(38)(39)(40)(41). Whereas, most evidence has demonstrated that a later chronotype is associated with mood disruptions such as depressive symptoms (38), some prior work suggests that earlier wake onsets may be indicative of heightened mood disruption (39).…”
Section: Discussionmentioning
confidence: 99%
“…Even excluding some effects of social factors like shift work, evening chronotype was found to be related to a higher incidence of depression (investigated in 1165 non-shift workers by Taillard et al, 2001 ). A recent meta-analysis of 43 studies demonstrated a reliable association between evening chronotype and depressive symptoms ( Norbury, 2021 ). A large population-based study of 10,503 adults indicated that evening chronotypes are at higher risk of having depressive disorders, needing to take antidepressant medication, and experiencing depressive symptoms ( Merikanto et al, 2015 ).…”
Section: Association Between Chronotype and Psychiatric Disordersmentioning
confidence: 99%